Propuesta de guía metodológica para la gestión de proyectos en el departamento de Servicio de ZEBOL S.A. - Solís-Castillo, Jorge Adrián (Instituto Tecnológico de Costa Rica, 2015)
This work is performing in ZEBOL, a company that sells pumping equipment since 1988. Specifically, the work takes place in a service department that exists within the company itself that is responsible for the management and project implementation. These projects are generated through the sale of pumping equipment, that require within the scope of the customer, the installation or placement of the equipment and complementary elements to make that your pumping system operates properly. However, the management and implementation of these projects has been inadequate, since there are no successful projects in scope, time and cost, being the last one, the one with more impact. To determine the current status of the company, an analysis of the degree of maturity in project management in the service department was conducted. The project management maturity model of Kerzner (2001) was used for this purpose, and just the first three levels were applied. The application of questionnaires for the first three levels in the service department was conducted to the CEO, the COO and project supervisors. Once all the information was collected, it was processed and an analysis of the data was performed. Within the information obtained in the analysis is the need for methodological guidelines for the management and implementation of projects and the need for some training of the staff in the service department ZEBOL in project management. As a result of the evaluation of project management maturity model levels of Kerzner (2001), was the identification of the phases of the life cycle of projects, what groups of processes are involved at each stage and what areas of knowledge are involved in these processes. Once the information was obtained, became a sort of it to have a clearer vision of how they manage and implement the projects currently in the service department ZEBOL. Within the information obtained was the identification of three stages in the life cycle of projects that are 1) proposal 2) Project development and 3) Maintenance. After analyzing the current situation of the service department, proceeded with the approach of the desired situation. In the current situation was determined that there is a need to manage and execute projects as a unified manner and under the same language. Therefore, a proposed xvi methodological guide for project management in the service department of ZEBOL was developed. The methodological guide includes a tool in Microsoft Excel with templates for ease use and access to information when required. Finally, the proposal for the desired situation culminates with a plan for implementation of the proposed methodological guide, which provides information on who should be trained and the time required for training. KEY WORDS: Service department, Project management, Project management methodology
Proyecto de graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos Maestría en Gerencia de Proyectos. 2015.
Keywords: Servicios; Gestión; Proyectos; Administración; ZEBOL